2019
DOI: 10.1029/2019jd030665
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Australian Heatwaves via Local Land‐Atmosphere Coupling

Abstract: Key Points Spatial variability in the land‐atmosphere coupling defines local heatwave sensitivity to antecedent land surface conditions Land‐driven coupling regions experience a higher heatwave day frequency with temperatures sensitive to prior soil moisture conditions Antecedent soil moisture anomaly rather than drying rate 2 weeks prior to a heatwave has a longer impact on heatwave temperatures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 77 publications
1
55
0
Order By: Relevance
“…I A is higher in magnitude for SWWA as compared to SEA, and also higher over a larger area in SWWA as compared to SEA, which explains the stronger response. This is consistent with previous work examining land-atmosphere coupling strength over Australia which has also identified SWWA as a hot-spot and weaker coupling over SEA (Hirsch et al, 2019a(Hirsch et al, , 2015b(Hirsch et al, , 2014.…”
Section: Cooling Mechanismsupporting
confidence: 92%
See 3 more Smart Citations
“…I A is higher in magnitude for SWWA as compared to SEA, and also higher over a larger area in SWWA as compared to SEA, which explains the stronger response. This is consistent with previous work examining land-atmosphere coupling strength over Australia which has also identified SWWA as a hot-spot and weaker coupling over SEA (Hirsch et al, 2019a(Hirsch et al, , 2015b(Hirsch et al, , 2014.…”
Section: Cooling Mechanismsupporting
confidence: 92%
“…Positive I A values imply that changes in HFX drive changes in TMAX and denote a "land-driven" regime, whereas negative values denote an "atmosphere-driven" regime. Following Hirsch et al (2019a), I A values are normalized by subtracting the spatial mean and dividing by the spatial standard deviation for ease of interpretation, and values greater than 0.2 denote strong land-atmosphere coupling. Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Andrys et al (2015) showed that the WRF model was able to adequately simulate the climate of SWA, and these simulations have also been used to assess the impacts of current and future climate on temperature and precipitation (Andrys et al, 2016(Andrys et al, , 2017 as well as climate indices relevant to viticulture for SWA (Firth et al, 2017). The WRF simulations of Andrys et al (2015) have also been benchmarked against other regional climate model simulations across the Australian continent and shown to perform well in simulating both temperature and precipitation (Di Virgilio et al, 2019) as well as heat-wave events (Hirsch et al, 2019). For the years before 1981 the weather conditions measured at the nearby Halls Head weather station (4.2 km away from the Mandurah station) were used.…”
Section: Climate Change Context and Simulation Rationalementioning
confidence: 99%